Determining the knowledge, attitudes, beliefs and practices of the adult consumer in the City of Cape Town, Western Cape, South Africa, regarding the inclusion of genetically modified foods in the diet - Jonker, Kari (Stellenbosch : Stellenbosch University, 2017)
Thesis (MNutr)--Stellenbosch University, 2017.